Analisis Closed Circuit Television (CCTV) Berbasis IOT dalam Mendukung Keselamatan Penerbangan di Unit Apron Movement Control (AMC) di Bandar Udara Internasional Komodo - Anggaraini Putri, Emy; Hilal, Raden Fatchul (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the role of Closed Circuit Television (CCTV) based on the Internet of Things (IoT) in supporting flight safety at the Apron Movement Control (AMC) unit of Komodo International Airport, Labuan Bajo. This research also identifies the common obstacles encountered in implementing IoT-based CCTV systems for monitoring and aviation safety. The research uses a qualitative approach with data collected through interviews, observation, and documentation. Three informants from the AMC unit, including the Head, Junior Staff, and Officer, provided the data. The results show that IoT-based CCTV plays a crucial role in enhancing real-time surveillance, detecting operational violations, and improving response time to incidents in the apron area. This technology enables broader monitoring coverage, including hard-to-reach areas. However, some challenges still exist, such as limited camera coverage, blind spots, equipment malfunctions, and poor image quality during nighttime or adverse weather. These issues can be addressed by adding more CCTV units, conducting regular maintenance, upgrading camera quality, and providing ongoing training for personnel. It is recommended that airport management immediately improve the IoT-based CCTV system by increasing camera installations in uncovered areas, strengthening the network system, and utilizing cloud storage to support digital data processing. These improvements can enhance monitoring effectiveness and readiness for potential risks in the apron area, thereby optimizing aviation safety.